FINANCIAL LITERACY AND FINANCIAL ATTITUDE TOWARDS FINANCIAL MANAGEMENT BEHAVIOR OF UMKM IN PACKAGING CULINARY SECTOR IN PADANG BARAT DISTRICT - Marbun, Innocencia; Sari, Laynita; Septiano, Renil (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
SMEs in Indonesia are the foundation of people's economic development. This shows that SMEs are one of the business sectors that can grow and remain consistent in the national economy. The purpose of this research is to determine whether financial literacy and financial attitudes affect the financial management behavior of SMEs in the packaged culinary sector in Padang Barat District. This study uses a quantitative approach and the sampling technique used is convenience sampling. This research involves a sample of 75 SME actors, with 66 data responses received. Data was obtained from questionnaires distributed to SME actors in the packaged culinary sector in Padang Barat District. Data processing was conducted using SPSS version 26. The results of this study explain that financial literacy has a positive and significant effect on financial management behavior, while the results of the study show that financial attitudes do not affect financial management behavior.